Honokiol improves depression-like behaviors in rats by HIF-1α- VEGF signaling pathway activation - Fan, Xiao-Xu; Sun, Wen-Yan; Li, Yu; Tang, Qin; Li, Li-Na; Yu, Xue; Wang, Shu-Yan; Fan, Ang-Ran; Xu, Xiang-Qing; Chang, Hong-Sheng (Frontiers in Pharmacology, 2022)
Increasing evidence indicates that the pathogenesis of depression is closely linked to impairments in neuronal synaptic plasticity. Honokiol, a biologically active substance extracted from Magnolia Officinalis, has been proven to exert significant antidepressant effects. However, the specific mechanism of action remains unclear. In this study, PC12 cells and chronic unpredictable mild stress (CUMS) model rats were used to explore the antidepressant effects and potential mechanisms of honokiol in vitro and in rats. In vitro experiment, a cell viability detection kit was used to screen the concentration and time of honokiol administration. PC12 cells were administered with hypoxia-inducible factor-1α (HIF-1α) blocker, 2-methoxyestradiol (2-ME), and vascular endothelial growth factor receptor 2 (VEGFR-2) blocker, SU5416, to detect the expression of HIF-1α, VEGF, synaptic protein 1 (SYN 1), and postsynaptic density protein 95 (PSD 95) by western blotting. In effect, we investigated whether the synaptic plasticity action of honokiol was dependent on the HIF-1α-VEGF pathway. In vivo, behavioral tests were used to evaluate the reproducibility of the CUMS depression model and depression-like behaviors. Molecular biology techniques were used to examine mRNA and protein expression of the HIF-1α-VEGF signaling pathway and synaptic plasticity-related regulators. Additionally, molecular docking techniques were used to study the interaction between honokiol and target proteins, and predict their binding patterns and affinities. Experimental results showed that honokiol significantly reversed CUMS-induced depression-like behaviors. Mechanically, honokiol exerted a significant antidepressant effect by enhancing synaptic plasticity. At the molecular level, honokiol can activate the HIF-1α-VEGF signaling pathway in vitro and in vivo, as well as promote the protein expression levels of SYN 1 and PSD 95. Taken together, the results do not only provide an experimental basis for honokiol in the clinical treatment of depression but also suggest that the HIF-1α-VEGF pathway may be a potential target for the treatment of depression.